INDUSTRY 4.0 AND THE CIRCULAR ECONOMY: ARE THESE INTEGRATED OR DISJOINTED CONCEPTS? A RESEARCH AGENDA - Agudo, Fabiana Liar; Gobbo Júnior, José Alcides; Oliveira Gobbo, Simone Cristina de (Revista Gestão da Produção Operações e Sistemas, 2020)
Purpose - To analyze whether the concepts of industry 4.0 and the circular economy are integrated or disjointed, recognizing which keywords are most used in the literature regarding this relationship and the occurrence. Design/methodology/approach – A bibliometric study and keyword study were used to recognize which were the most latent actions and strategies in the study of integration. The software VOSviewer was used to study the keywords. Findings - The concepts of industry 4.0 and the circular economy can be considered interconnected, with some limitations explored in the article, along with proposed future research opportunities on the subject. Originality/value - This study contributes to business managers in the sense that it facilitates an understanding that industry 4.0 and the circular economy can be used together. The result of the keywords identifies which skills, strategies, technologies and fundamentals the company should develop to make the circular economy effective, through industry 4.0. For academic research, another study has contributed to the integration of industry 4.0 and the circular economy, which is not found very often in the literature. Keywords were also mapped, which, until now, had not been developed in existing articles on integration, in addition to proposing a framework that can be transformed and suggesting research opportunities. Keywords - Industry 4.0; Circular Economy; Integration; Sustainability; Future research.